Resolved-sideband Raman cooling of an optical phonon in semiconductor materials - Zhang, Jun (2020)
The radiation pressure of light has been widely used to cool trapped atoms or the mechanical vibrational modes of optomechanical systems. Recently, by using the electrostrictive forces of light, spontaneous Brillouin cooling and stimulated Brillouin excitation of acoustic modes of the whispering-gallery-type resonator have been demonstrated. The laser cooling of specific lattice vibrations in solids (that is, phonons) proposed by Dykman in the late 1970s, however, still remains sparsely investigated. Here, we demonstrate the first strong spontaneous Raman cooling and heating of a longitudinal optical phonon (LOP) with a 6.23 THz frequency in polar semiconductor zinc telluride nanobelts. We use the exciton to resonate and assist photoelastic Raman scattering from the LOPs caused by a strong exciton-LOP coupling. By detuning the laser pump to a lower (higher) energy-resolved sideband to make a spontaneous scattering photon resonate with an exciton at an anti-Stokes (Stokes) frequency, the dipole oscillation of the LOPs is photoelastically attenuated (enhanced) to a colder (hotter) state.